(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2025)
Ketorolac tromethamine and rabeprazole sodium are drugs that are used frequently, and certain clinical conditions warrant their concomitant use. Ketorolac has been known to engage in physical interactions with several drugs that share certain structural features with rabeprazole, and therefore their degree of chemical association was assayed. 0.05 mM solutions of the two drugs were prepared with buffer solutions of pH 1.4, 2.4, and 7.4. Conductometric titrations were conducted for each. The two drugs were observed to form chemical associations with each other on a nearly 1:1 basis in each buffer solution. Sharp breaks in all cases were recorded. Ketorolac has previously been reported to form intermolecular interactions with drug moieties containing amine groups with non-engaging lone-pair electrons, and this was postulated to be the mechanism of action for the interaction. As certain clinical conditions can warrant the concomitant use of these two drugs, additional care must be taken in such cases to avoid unfavorable clinical complications. Dhaka Univ. J. Pharm. Sci. 24(1): 87-94, 2025 (June)